Comparison of conventional and supported liquid extraction methods for the determination of sitagliptin and simvastatin in rat plasma by LCâESIâMS/MS - B. Ramesh; N. Manjula; S.R. Bijargi; V.U.M. Sarma; P. Sita Devi (Elsevier, 2015)
Three extraction methods were compared for their efficiency to analyze sitagliptin and simvastatin in rat plasma by LCâMS/MS, including (1) liquidâliquid extraction (LLE), (2) solid phase extraction (SPE) and (3) supported liquid extraction (SLE). Comparison of recoveries of analytes with different extraction methods revealed that SLE was the best extraction method. The detection was facilitated with ion trap-mass spectrometer by multiple reactions monitoring (MRM) in a positive ion mode with ESI. The transitions monitored were m/z 441.1â325.2 for simvastatin, 408.2â235.1 for sitagliptin and 278.1â260.1 for the IS. The lower limit of quantification (LLOQ) was 0.2Â ng/mL for sitagliptin and 0.1Â ng/mL for simvastatin. The effective SLE offers enhanced chromatographic selectivity, thus facilitating the potential utility of the method for routine analysis of biological samples along with pharmacokinetic studies. Keywords: Rat plasma, Simvastatin, Sitagliptin, Supported liquid extraction